Computer science - Brookshear, J. Glenn (Addison Wesley, 2003)
Includes bibliographical references and index; Introduction - Data storage - Data Manipulation - Operating systems - Networking and the Internet - Algorithms - Programming languages - Software Engineering - Data Abstractions - Database systems - Computer Graphics - Artificial intelligence - Theory of computation